2008
DOI: 10.1016/j.stem.2008.09.001
|View full text |Cite
|
Sign up to set email alerts
|

The Systematic Production of Cells for Cell Therapies

Abstract: Stem cells have emerged as the starting material of choice for bioprocesses to produce cells and tissues to treat degenerative, genetic, and immunological disease. Translating the biological properties and potential of stem cells into therapies will require overcoming significant cell-manufacturing and regulatory challenges. Bioprocess engineering fundamentals, including bioreactor design and process control, need to be combined with cellular systems biology principles to guide the development of next-generati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
210
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 277 publications
(212 citation statements)
references
References 128 publications
(125 reference statements)
1
210
0
1
Order By: Relevance
“…The comprehension and optimization of the expansion and differentiation process of HMSCs will contribute to maximi-zation of cell yield, reduction of cell culture and a decrease of total process costs ( Gong et al, 2009;Kirouac and Zandstra, 2008). In culture conditions, cells consume mostly glucose as substrate for the generation of cellular energy (ATP).…”
Section: Groupmentioning
confidence: 99%
“…The comprehension and optimization of the expansion and differentiation process of HMSCs will contribute to maximi-zation of cell yield, reduction of cell culture and a decrease of total process costs ( Gong et al, 2009;Kirouac and Zandstra, 2008). In culture conditions, cells consume mostly glucose as substrate for the generation of cellular energy (ATP).…”
Section: Groupmentioning
confidence: 99%
“…23 For tendon repair, previous studies in rodents showed that at least 10 6 BMSCs were required, 3,5,24 so it is not surprising that many more cells are needed in human patients. An optimized strategy for the in vitro expansion of stem cells while maintaining their undifferentiated stem cell characteristics is therefore essential.…”
Section: Discussionmentioning
confidence: 99%
“…Closed culture/expansion systems have been developed to exchange medium in large capacity tissue culture flasks using stopcocks and gravity-based flow to minimize the risk of operator error during the culture expansion process [4]. Bioreactors with controlled flow rates and built in monitors for cell viability, lactate production, pH/ pO 2 , and glucose levels need to be made efficient, practical, and scalable to current and future needs [7]. The use of automated, computer-controlled devices has the potential to reduce the risk of operator error during the culture period.…”
Section: Closed System Manufacturing Devicesmentioning
confidence: 99%